Terapeutik Berbasis Nilai Nilai sebagai Pendekatan Guru untuk Membantu Masalah Perilaku Siswa - Mardiana, Puja; Khoiriah, Hanifathu; Rosyid, Imron; Ahadiakbar , Gebyar; S, Endang (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
The implementation of Islamic values-based therapeutics is very important in an Islamic educational institution.  This is due to the increasing behavioral and emotional challenges faced by students. Therefore, a therapeutic approach that integrates Islamic values is expected to help students in the process of self-healing and character development. The research method used is qualitative with a case study design, which allows researchers to gain an in-depth understanding of this practice. The subjects of this study were Mas Yapen Teachers and Students consisting of 10 teachers and 30 Students.  Data was collected through observation, in-depth interviews with teachers and students, and document studies related to Mas Yapem. Observations were conducted to understand interactions in the educational environment, while in-depth interviews provided insight into participants' experiences and perceptions. The data analysis technique used the thematic analysis method, in which the data obtained would be categorized and the main themes identified. Triangulation of sources and methods was used to enhance the credibility of the findings. The results of the study are expected to provide practical recommendations for Mas Yapem and other Islamic educational institutions in implementing Islamic values-based therapeutic approaches effectively and sustainably, so as to help students overcome psychological and emotional problems better